Analyzing the Structure-Conduct-Performance of the Tofu Industry in Banda Aceh - Lubis, Putra Fisabilillah; Romano, Romano; Rusdi, Muhammad (International Journal Labs, 2022)
Background: At this time the food industry sector is growing very rapidly and increasing fierce competition among business people such as the tofu industry in Banda Aceh City. This encourages the importance of the application of SCP in describing the overall state of the market both the structure, behavior, and performance resulting from industry. Aim: This research aims to describe the structure, behavior, and performance of the industry as well as the influence of these three dimensions on the tofu industry in Banda Aceh City. Method: This study uses a quantitative approach and uses a census method where the population is all tofu producers registered with the Banda Aceh City Labor Office in the industrial section of 2019-2020 which amounted to 13 industries. CR4 and IHI analysis is used to measure structure, CLR analysis is applied to measure behavior, and PCM is used to improve the performance of the tofu industry in Banda Aceh City. The effect test on 3 dimensions is measured using Path Analysis. Findings: Found CR4 values 36.43 percent, IHI 729.99 points, CLR 11.06 percent, and PCM 12.08 percent. As well as found the relationship of variable MS to PCM positive and significant, clr relationship to positive PCM is not significant and the relationship of MS to PCM through positive CLR is not significant.